Cancer After Pediatric Kidney Transplantation: A Long-term Single-center Experience in Japan. Issue 4 (April 2021) - Yabuuchi, Tomoo; Miura, Kenichiro; Shimizu, Satoru; Kaneko, Naoto; Ishizuka, Kiyonobu; Kanda, Shoichiro; Chikamoto, Hiroko; Akioka, Yuko; Fujieda, Mikiya; Hattori, Motoshi
Abstract : Background: The cancer incidence, types, and risk factors after pediatric kidney transplantation (KT) have been reported in the United States, Canada, Europe, Australia, and New Zealand. However, no information is available about cancer in pediatric KT recipients in Asian countries. Methods: Children aged <20 y who underwent initial KT from 1983 to 2016 were analyzed. We compared the cancer incidence with that in the general Japanese population using standardized incidence ratio and examined posttransplant cancer risk using Cox proportional hazards models. Results: A total of 356 children (median age, 11.7 y; interquartile range, 5.0–17.6) received KT with a follow-up period of 4466 person-years. The median age of cancer onset was 18.5 y (interquartile range, 8.0–32.3), and 13 cancers occurred in 12 patients (3.4%). Two patients died from cancer. The most common cancers were posttransplant lymphoproliferative disorders (PTLDs) (38.5%). The median time to PTLD and non-PTLD diagnosis after KT was 0.6 and 16.4 y, respectively. There was no occurrence of skin cancer. The posttransplant cancer incidence was 9.9 times higher than that in the general age-matched population (standardized incidence ratio = 9.9; 95% confidence interval, 4.80-18.39). The cumulative cancer incidence was 5.3% in 20 y after KT, which is lower than that reported in previous studies. We could not identify any risk factors for all cancer after KT in all patients, whereas subgroup analysis in 264 patients with available data of recipient Epstein-Barr virus serological status showed that recipient Epstein-Barr virus-negative serology was an independent risk factor for cancer development. Conclusions: The incidence of cancer is higher in Japanese pediatric KT recipients than in the general population. The cumulative incidence of cancer after KT was lower in our population than that previously reported. This may be because there was no skin cancer observed in the Japanese pediatric KT recipients in our study. Abstract : Supplemental Digital Content is available in the text.